Desodorante e sabão artesanal na Educação de Jovens e Adultos: Uma possibilidade em educação ambiental a partir do programa etnomatemática - Peixoto, Cinara Ribeiro (2024)
This research describes an intervention developed and carried out with students from the Youth and Adult Education (EJA) program at a municipal public school in Uberlândia/MG. Two practices are articulated: the production of natural deodorant and the production of handmade soap from reused oil. Permeating the theorizations of D'Ambrósio's Ethnomathematics Program (2018), the research arose from the need for financial resources due to professional instabilities as a result of the covid-19 pandemic and is configured as a proposal to carry out practices based on a critical analysis of environmental issues, in order to involve students in changing attitudes related to the environment and establishing collectivity and cooperation from the perspective of Solidarity Economy. The main subject of this proposal was the processes involved in producing handmade soap and natural deodorant, linked to the content of mathematics. The general objective is to enable the constitution of knowledge in the production of natural deodorant and handmade soap with EJA students, seeking interfaces between Mathematics and Environmental Education from the perspective of the Ethnomathematics Program and Solidarity Economy. Characterized as qualitative action research, the intention is to investigate: What knowledge and meanings can be built up with EJA students, based on the relationship between mathematics and environmental education through procedures involving the production of natural deodorant and handmade soap? Based on these considerations, an educational product called “Breaking ‘epistemological cages’ at EJA: dialogues between the production of homemade soap and deodorant from the perspective of ethnomathematics” was developed using the Project Learning methodological approach. This material is intended for educators and covers activities related to environmental issues in the context of mathematics, as well as providing recipes for soap and deodorant production. The investigation revealed that the proposed initiatives have become firmly established in this school unit as a consolidated project. The students show an appreciation for different learning approaches, showing interest in activities that are applicable to everyday life and aligned with their expectations, meeting their concerns. The project has been running since 2021 and currently serves as a source of funds for additional activities with the students, such as biannual visits to the cinema, technical outings and graduation events.